RANCANG BANGUN APLIKASI PELAYANAN ADMINISTRASI PUBLIK PADA KANTOR KELURAHAN MAJASARI BERBASIS WEBSITE - Muhammad Wilian Harlangga; Ariansyah; Andi Christian (Elkom: Jurnal Elektronika dan Komputer, 2023)
The Majasari Village Official is one of the Government institutions located in the Majasari sub- district. The way public administration services are currently carried out is stil running with a manual system, which stil uses Microsoft Word and Excel document processing applications or notebooks in public administration services. So that in the public service process errors often occur and the reporting process and report results are late. This application was built using a web with the PHP programming language and Mysql informasi base, and to print the repost using a pdf component. Based on the test results, it can be concluded that this system is able to provide fast and accurate services because it is well computerized and easy to use.